The Implementation of Management Rights for Ethereum Forking Governance - Wong Wai Wai (International Journal of Advanced Science and Technology, 2020)
Ethereum is an open-source, decentralized applications to support a cryptocurrency-based trading platform. The recent Ethereum hard fork, called ‘Istanbul’ took place in October 2019 due to threats from multitude of competitors has been completed. This hard fork brings six Ethereum Improvement Proposals (EIPs) which includes code execution, blockchain’s mining algorithm, increase data storage process capacity and also reduce Gas costs. Although these changes intended to improve the performance of Ethereum blockchain, many people have raise concern that forking is controversial. Cryptocurrency forks usually brings big changes ahead and may have serious implication on the price of Ethereum. Many resource appropriators (coin holders) are anxious about when will be the next network update for Ethereum. Most of the rules and decisions are made before these participants join the system or leave in the hands of developers of the project. There is lack of effective means for most resource appropriators or stakeholders to participate in system of decision-making for the next network update. This article provides a comprehensive overview of how decision-making for network update to be made in Ethereum and to propose the implementation of the management rights concerning the design, implementation of future changes to the Ethereum platform in order to achieve a clear collective-choice arrangement that allow most resource appropriators and stakeholders to participate in the decision-making process within the Ethereum community.